Synergistic Effects of Vitamin A and Spirulina on Arsenic Load in Rat Tissues and Blood (Research in Agriculture Livestock and Fisheries, 2024)
Arsenic (As) is found in contaminated groundwater as the source of pollution. In this study, 60 Long-Evans rats were used to assess the levels of As in the blood and organs and to compare the effectiveness of vitamin A and spirulina (Spirulina platensis) in preventing a chronic As accumulation. Twelve rats were assigned to each group of animals. The experimental groups were the control (T0), As (T1), As + spirulina (T2), As + vitamin A (T3), and As + spirulina + vitamin A (T4). The T1, T2, T3, and T4 groups were orally administered with sodium arsenite (NaAsO2) @ 4 mg/kg body weight (BW) for 63 days. In addition to NaAsO2, the T2 and T4 received 1 g/kg BW spirulina. The T3 and T4 received 2500 IU/kg BW vitamin A for 63 days, respectively. Four rats were euthanized in each group to evaluate the As concentration in the liver, lung, kidney, and blood at an interval of 21 days. Total As concentration was quantified from the organs using Hydride Generation Atomic Absorption Spectrophotometer (HG-AAS). The results revealed that the T0 had no visible clinical symptoms. However, after 63 days of treatment, the T1 (As only administration) accumulated more As compared to other groups. The concentration of As was highest in the blood, then in the kidney, liver, and lung. In this case, spirulina and vitamin A substantially (p